Tingkat Partisipasi Olahraga Kalangan Remaja Di Kota Palopo : Dampak Media Sosial - Aan Hardiyansah; Kahar, Irsan; Hidayat, Rachmat; Burhan, Ahmad Syarif (Universitas Hamzanwadi, 2025)
The level of youth participation in sports in Indonesia needs attention, while on the other hand, the use of social media in the lives of young people is becoming increasingly widespread. This situation raises questions about whether there is a relationship between these two phenomena, particularly in the city of Palopo. This study aims to analyze the influence of social media use on the level of youth participation in sports in the city. A quantitative approach was applied using a survey method with an online questionnaire (Google Form) distributed to 100 adolescents aged 10-24 years as a sample, selected using purposive sampling. The collected data were analyzed using descriptive statistics and tested using Spearman's correlation and simple linear regression. The results showed that there was no significant relationship between social media use and sports participation (p = 0.291 > 0.05). Further regression analysis also confirmed that there was no significant effect (p = 0.881 > 0.05), with an R² value of 0.034. The conclusion of this study is that social media use does not significantly affect youth sports participation in Palopo City, where only 3.4% of the variation in sports participation can be explained by social media, while the remaining 96.6% is influenced by other factors.